Pemberdayaan UMKM dengan Penerapan Etika Bisnis Islam di Desa Lengkese Kec. Manggarabombang Kab. Takalar - Ifnah, Nur; Leli; Paewai , Rusman (Indra Institute Research & Publication, 2024)
Currently, there are still many Muslim UMKM who run their businesses not by Islamic ethics. This activity aims to empower UMKM in Lengkese Village by applying Islamic business ethics. Islamic business ethics are expected to guide UMKM in running their businesses based on honesty, justice, responsibility, and balance. Several steps in this PkM activity are: (1) Preparation, (2) Implementation, and (3) Report writing. The method used in this service program is intensive training and mentoring for UMKM regarding the principles of Islamic business ethics and their implementation in daily activities. The results of this activity will be an understanding and awareness of UMKM players regarding the importance of ethics in business, which will have an impact on improving the quality of products and services, as well as better relationships with consumers and business partners. Thus, applying Islamic business ethics can be essential in encouraging the development of more sustainable and highly competitive UMKM.